The Significance of Endometrial Scratching for Clinical Pregnancy Rate in Long Agonist and Antagonist Protocols - Gricius, Rimantas (Medicina (Kaunas), 2019)
Background and Objectives: Assisted reproductive techniques today have helped many infertile couples achieve their desired pregnancy. However, unsuccessful implantation is usually the key failure in in vitro fertilization cycles. Many factors are now being studied to improve the implantation rate, one being endometrial artificial injury (endometrial scratching). The purpose of this study was to assess whether local endometrial artificial injury improved pregnancy rate, in long agonist and antagonist protocols. Materials and Methods: A retrospective analysis was carried out at the JSC Baltic American Clinic from January 1, 2016 to December 31, 2018. Women who were undergoing in vitro fertilization treatment were enrolled in the study. Medical data including demographic factors, menstrual history, and anamnesis of infertility were collected from medical records. Subjects were divided into intervention and control groups. The outcome of this study was clinical pregnancy rate (CPR). Results: A total of 137 women presenting with primary or secondary infertility were enrolled in the study. Clinical pregnancy was observed in 44/71 (61.9%) patients in the intervention group and 33/66 (50%) in the group without endometrial scratching (p value = 0.16). CPR in the intervention group was significantly higher in the patient group that had undergone ovarian stimulation with a long agonist protocol rather than the antagonist protocol (73.8% vs. 41.4%; p value = 0.006). In the multivariable logistic regression model, previously failed in vitro fertilization (IVF) (odds ratio (OR) = 0.07, 95% confidence interval (CI) 0.01–0.47), stimulation with the long agonist protocol (OR = 19.89, 95% CI 3.57–18.63), antagonist protocol (OR = 0.05, 95% CI 0.01–0.34), number of embryos (OR = 1.37, 95% CI 1.05–1.38), and number of blastocysts (OR = 2.96, 95% CI 1.43–8.36) remained important independent prognostic factors for clinical pregnancy. Conclusions: Our study findings indicate that randomized controlled studies are required to define patients for this procedure and to prove the effect and safety of local endometrial injury, before it is introduced to routine clinical practice.